THE VALIDITY OF UNILATERAL CANCELLATION BY THE CUSTOMER IN SHOPEE CASH ON DELIVERY TRANSACTIONS ACCORDING TO ISLAMIC ECONOMIC LAW - Fadhlurrahman, Raihan (JURISTA: Jurnal Hukum dan Keadilan, 2017)
Basically, the cancellation system on Shopee is designed to protect the interests of buyers and sellers and ensure that transactions on Shopee run smoothly. In practice, problems often occur, namely unilateral cancellation by the buyer. Buyers often refuse payment for orders that should be made via courier. Cases like this certainly make business actors feel disadvantaged because buyers cannot fulfill the agreements that have been made since the beginning of the order. In a transaction, the consumer unilaterally cancels the goods the seller has ordered. In this context, the customer has committed a default. The aim of this research is to determine the causes of unilateral cancellations by Shopee consumers in Cash On Delivery transactions, as well as to analyze the insights of Muamalah Fiqh regarding the unilateral cancellation mechanism by Shopee consumers in Cash On Delivery transactions from the Khiyār 'aib perspective. The type of research that researchers used in this research is descriptive analysis. The data sources used are primary data sources, namely Shopee customers (buyers) and Shopee sellers (sellers), then secondary data sources, namely the Shopee application, previous theses, and other supporting books. The data collection techniques used were interviews and documentation. The results of this research show that there are 5 reasons for unilateral cancellation, namely changes in personal thoughts, financial limitations, ordering errors, lack of understanding of the COD payment system, and late delivery. Then, in Fiqh Muamalah's observations, Khiyār 'aib's view in COD transactions at Shopee refers to the possibility of rejecting the transaction or refusing to accept the goods after seeing the condition of the goods received. If buyers want to use Khiyār 'aib in COD transactions on Shopee, they must immediately contact Shopee or follow the goods return procedures established by Shopee.